Assessment of the Relationship Between Thinness Expectations, Body Satisfaction and Eating Attitude and Behavior - Nural Erzurum Alim; Zehra Nur Beşler; Gözde Çalışkan; Kerim Kaan Göküstün (Amerta Nutrition, 2021)
Background: Body dissatisfaction is more common in adolescents and its prevalence is increasing in developed and developing countries. These situation is associated with unhealthy dieting behaviors. Purpose: This study aimed to evaluate the relationship between thinness expectations, body satisfaction, and eating attitudes and behaviors in interpersonal interaction.Method: This study was conducted on 372 university students. The survey form was prepared using the Google Surveys Program. In the questionnaire form, there are sociodemographic characteristics, anthropometric measurements, Interpersonal Outcome Expectancies for Thinness (IOET), Nutritional Changes Process Scale (NCPS), and Body Shape Questionnaire (BSQ).Result: There was no statistically significant difference in the mean total scores of the IOET, BSQ, and NCPS scales according to gender (p > 0.05). According to the NCPS scale sub-dimensions, it was determined that the means scores of dramatic relief and social liberation were higher in females than males (p < 0.05). However, the mean scores of reinforcement management, stimulus control, interpersonal control systems, and substance abuse were lower in females than males (p < 0.05). In addition, when the distribution of thinness was examined in the relationships with family, other family members, teachers, friends, colleagues, and foreigners according to gender, it was determined that there was no statistically significant difference (p > 0.05). The findings show that there were moderate and strong positive correlations between the total score of BSQ and NCPS, and IOET total scores, respectively (p < 0.05).Conclusion: According to the study results, body shape is important in interpersonal relationships among university students and body dissatisfaction may be related to eating behaviors.